Personnel training for the defense-industrial complex of Russia: problems and ways of their solution - Sergey N. Grigoriev; Yuliya Y. Eleneva (Высшее образование в России)
In this article the key problems of personnel development in the sphere of the defense-industrial complex of the Russian Federation are treated in accordance with all participants of the development process of defense industry human resources. The system of first-priority, tactic and strategic arrangements aimed at improvement of defense industry personnel training and retraining is also provided. The concept of educational clusters is proposed as one of the directions of development of the defense-industrial personnel potential. The empirical data is obtained from MSTU “STANKIN” experience and the research carried out by Russian Engineering Union in 2012.